Patterns and Determinants of Treatment Seeking among Previously Untreated Psychotic Patients in Aceh Province, Indonesia: A Qualitative Study - Marthoenis Marthoenis; Marion C. Aichberger; Meryam Schouler-Ocak (Scientifica)
Immediate treatment of first-episode psychosis is essential in order to achieve a positive outcome. However, Indonesian psychiatric patients often delay accessing health services, the reason for which is not yet fully understood. The current study aimed to understand patterns of treatment seeking and to reveal determinants of the delay in accessing psychiatric care among first-time user psychotic patients. Qualitative interviews were conducted with sixteen family members who accompanied the patients to a psychiatric hospital. Many families expressed beliefs that mental illness appertains to village sickness and not hospital sickness; therefore, they usually take the patients to traditional or religious healers before taking them to a health professional. They also identified various factors that potentially delay accessing psychiatric treatment: low literacy and beliefs about the cause of the illness, stigmatisation, the role of extended family, financial problems, and long distance to the psychiatric hospital. On the other hand, the family mentioned various factors related to timely help seeking, including being a well-educated family, living closer to health facilities, previous experience of successful psychotic therapy, and having more positive symptoms of psychosis. The findings call for mental health awareness campaigns in the community.